2001
DOI: 10.1055/s-2001-19686
|View full text |Cite
|
Sign up to set email alerts
|

Topisches Mitomycin C zur Rezidivprophylaxe von Haze nach erneuter Excimer-Laser-photorefraktiver Keratektomie (PRK) - Klinische Pilotstudie an 5 Patienten1

Abstract: Topical applied mitomycin C seems to be a promising therapy to prevent recurrent haze after a second PRK procedure. As mitomycin C can be associated with a variety of serious complications, it should only be used in patients with high risk of haze.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The 9-month follow-up revealed that the surgically treated corneas remained clear. 18 Majmudar et al 31 demonstrated that topical application of mitomycin C (0.02%) successfully prevented the recurrence of epithelial fibrosis after debridement. Eight corneas undergoing mitomycin C treatment after debridement remained clear, with no recurrence or adverse reaction throughout the follow-up periods (6 -25 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 9-month follow-up revealed that the surgically treated corneas remained clear. 18 Majmudar et al 31 demonstrated that topical application of mitomycin C (0.02%) successfully prevented the recurrence of epithelial fibrosis after debridement. Eight corneas undergoing mitomycin C treatment after debridement remained clear, with no recurrence or adverse reaction throughout the follow-up periods (6 -25 months).…”
Section: Discussionmentioning
confidence: 99%
“…16 Mitomycin C reduces keratocytes in the anterior stroma after corneal refractive surgery, leading to a decrease in activated fibroblasts, production of extracellular matrix, and formation corneal haze. [17][18][19][20] Mitomycin C, an alkylating antibiotic agent derived from Streptomyces caespitosus, blocks DNA and RNA replication and protein synthesis. The compound is metabolized by liver enzymes to form an alkylating agent that nonspecifically crosslinks with DNA in a cell-cycle-dependent manner.…”
mentioning
confidence: 99%
“…Mitomycin C and steroids have been found to prevent corneal opacity, and the former has been effective in several clinical trials. [29][30][31][32] In this study, we tested ceramides to determine their effect on rabbit corneal fibroblasts.…”
Section: Cornea • Volume 24 Number 1 January 2005mentioning
confidence: 99%
“…[15][16][17][18][19][20] Based on its success in the treatment of symptomatic haze, MMC has been evaluated as a prophylactic agent for the prevention of haze following high-risk PRK. 21,22 We hypothesized that surface ablation over a LASIK flap with adjunctive MMC would result in excellent refractive outcomes and minimize the risk for postoperative corneal haze. We report 10 eyes of 10 patients with flap complications who had phototherapeutic keratectomy (PTK)/PRK followed by prophylactic use of MMC (PTK/PRK/MMC) with the intended refractive outcome of emmetropia.…”
mentioning
confidence: 99%